Nonlinear time series analysis - Bruce Mizrach (Rutgers University, Department of Economics, 2006)
This entry for the New Palgrave covers developments in nonlinear time series analysis over the last 25 years.
Keywords: C14; 330; Analysis; nonlinear; time series